PEST Analysis in the Implementation of the Social Assurance Agency for Health in Indonesia - Pamelleri, Resky Amalia; Rivai, Nur Ilmiah (International Journal of Social Science and Business, 2025)
The implementation of the Social Health Insurance Agency (Badan Pengelola Jaminan Sosial—BPJS Health) in Indonesia represents a major step toward achieving universal health coverage; however, it faces persistent challenges shaped by political, economic, social, and technological contexts. This research aims to examine the external factors influencing the performance and sustainability of BPJS Health through the application of the PEST (Political, Economic, Social, and Technological) analysis framework. A qualitative research design was employed, combining document analysis of government regulations, policy reports, and academic sources with expert interviews involving policymakers, healthcare practitioners, and scholars. Data were analyzed thematically using NVivo software, enabling the categorization of recurring themes across the four PEST dimensions. The findings reveal that political factors such as budget allocation, leadership commitment, and regulatory shifts significantly affect program sustainability, while economic challenges such as low contribution compliance, widespread poverty, and infrastructure disparities hinder financial resilience. Social aspects including low public awareness, inequality in access, and conflicts between stakeholders further complicate implementation, whereas technological limitations related to system integration, inadequate infrastructure, and digital literacy gaps restrict efficiency and innovation. Despite these challenges, opportunities exist through policy coordination, financial reforms, public awareness campaigns, and digital innovations such as telemedicine. In conclusion, the study highlights that the success of BPJS Health is contingent on the synergy of political will, economic inclusivity, social engagement, and technological advancement, providing valuable insights for strengthening Indonesia’s national health insurance system and ensuring equitable healthcare for all citizens.